Political feasibility of scaling-up five evidence-informed HIV interventions in Pakistan: a policy analysis. (23rd March 2009) - Buse, K; Lalji, N; Mayhew, S H; Imran, M; Hawkes, S J
Abstract : Background: Drawing on policy theories, an assessment was made of the perceived political feasibility of scaling-up five evidence-based interventions to curb Pakistan's HIV epidemic: needle and syringe exchange programmes; targeted behaviour change communication; sexual health care for male and transgender sex workers; sexual and reproductive health care for female sex workers; and promoting and protecting the rights of those at greatest risk. Method: A questionnaire was emailed to 40 stakeholders and completed by 22. They expressed their level of agreement with 15 statements for each intervention (related to variables associated with policy success). Semi-structured interviews were conducted with 12 respondents. Results: The interventions represent considerable change from the status quo, but are perceived to respond to widely acknowledged problems. These perceptions, held by the HIV policy elite, need to be set in the context of the prevailing view that the AIDS response is not warranted given the small and concentrated nature of the epidemic and that the interventions do not resonate closely with values held by society. The interventions were perceived to be evidence-based, supported by at least one donor and subject to little resistance from frontline staff as they will be implemented by contracted non-government organisations. The results were mixed in terms of other factors determining political feasibility, including the extent to which interventions are easy to explain, exhibit simple technical features, require few additional funds, are supported and not opposed by powerful stakeholders. Conclusion: The interventions stand a good chance of being implemented although they depend on donor support. The prospects for scaling them would be improved by ongoing policy analysis and strengthening of domestic constituencies among the target groups.